Atopic dermatitis in cats and dogs: a difficult disease for animals and owners - Gedon, Natalie Katharina Yvonne (Clin Transl Allergy, 2018)
The purpose of this review article is to give an overview of atopic dermatitis in companion animals and of recent developments including knowledge on immunological background, novel treatment options and difficulties in disease management. The prevalence of hypersensitivities seems to be increasing. The pathogenetic mechanisms are not fully understood, yet multiple gene abnormalities and altered immunological processes are involved. In dogs and cats, the diagnosis of atopic dermatitis is based on history, clinical examination and exclusion of other differential diagnoses. Intradermal testing or testing for serum allergen-specific Immunoglobulin E is only used to identify allergens for inclusion in the extract for allergen immunotherapy. Symptomatic therapy includes glucocorticoids, ciclosporin, essential fatty acids and antihistamines. A selective janus kinase 1 inhibitor and a caninized monoclonal interleukin-31 antibody are the newest options for symptomatic treatment, although longterm effects still need to be assessed. The chronic and often severe nature of the disease, the costly diagnostic workup, frequent clinical flares and lifelong treatment are challenging for owners, pets and veterinarians. Patience and excellent communication skills are needed to achieve a good owner compliance and satisfactory clinical outcome for the animal.